2022
DOI: 10.1039/d1sc06035j
|View full text |Cite|
|
Sign up to set email alerts
|

Catalytic asymmetric hydrometallation of cyclobutenes with salicylaldehydes

Abstract: Chiral, substituted cyclobutanes are common motifs in bioactive compounds and intermediates in organic synthesis but few asymmetric routes for their synthesis are known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…A range of cyclobutenes was used to provide the target products in up to 89% yield, >20:1 dr and 99% ee (Scheme 11d). 85 In 2008, enantioselective intermolecular hydroacylation of aryl and alkyl β-S-aldehydes 83 with racemic allenes (±)-84 was described by the Willis group (Scheme 12a). 86 Detailed mechanistic studies suggested that the isomerization of allenes occurred under the reaction conditions, showing a dynamic kinetic asymmetric transformation.…”
Section: Rh(i)-catalyzed Asymmetric Intermolecular Hydroacylationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of cyclobutenes was used to provide the target products in up to 89% yield, >20:1 dr and 99% ee (Scheme 11d). 85 In 2008, enantioselective intermolecular hydroacylation of aryl and alkyl β-S-aldehydes 83 with racemic allenes (±)-84 was described by the Willis group (Scheme 12a). 86 Detailed mechanistic studies suggested that the isomerization of allenes occurred under the reaction conditions, showing a dynamic kinetic asymmetric transformation.…”
Section: Rh(i)-catalyzed Asymmetric Intermolecular Hydroacylationsmentioning
confidence: 99%
“…Recently, Fletcher and co-workers reported a Rh­(I)-catalyzed asymmetric intermolecular hydroacylation of various meso -cyclobutenes with salicylaldehydes. A range of cyclobutenes was used to provide the target products in up to 89% yield, >20:1 dr and 99% ee (Scheme d) …”
Section: Rh(i)-catalyzed Asymmetric C–h Functionalization Reactionsmentioning
confidence: 99%
“…18 Subsequently, they reported a Rhcatalyzed process for enantioselective hydroacylation of unactivated cyclobutenes with salicylaldehydes via hydrometalation (Scheme 1b). 19 However, methods for incorporation of sp-and functionalized sp 3 -nucleophiles into fourmembered rings remained unknown. Herein, we disclosed a series of protocols for catalytic enantioselective carbon−carbon bond forming reactions of ester-substituted and unactivated cyclobutanes with cobalt homoenolates generated from cyclopropanols, alkynes, and potassium allyl trifluoroborate initiated by carbometalation promoted by readily available cobalt complexes (Scheme 1c).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The pioneering work on Rh-catalyzed arylation of cyclobutenes was revealed by Fletcher and co-workers (Scheme b) . Subsequently, they reported a Rh-catalyzed process for enantioselective hydroacylation of unactivated cyclobutenes with salicylaldehydes via hydrometalation (Scheme b) . However, methods for incorporation of sp- and functionalized sp 3 -nucleophiles into four-membered rings remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The same group also reported asymmetric Pt-catalyzed diborylation of spirocyclic cyclobutenes [9] and copper-catalyzed monoboration of spirocyclic cyclobutenes to yield achiral 3-substituted spirocyclobutanes (Figure 2A). [10] Buchwald and co-workers developed a CuH-catalyzed enantioselective hydroamination of 1-substituted cyclobu-tenes to give enantioenriched trans-1,2-disubstituted aminocyclobutanes (Figure 2A), [11] and Rh-catalyzed asymmetric hydroacylation of cyclobutenes [12] has also been reported, with both of these reactions believed to occur via a key asymmetric hydrometalation step.…”
mentioning
confidence: 99%